Isolation and identification of fungi from polluted soil in Peninsular Malaysia for copper remediation - Ong, Ghim Hock; Leeraj, Christopher; Soh, Joanne; Saikalsham, keeva; Wong, Ling Shing (EM International, 2017)
A total of 10 fungi were extracted from soil of Cu contaminated site in Peninsular Malaysia, with3 fungi have the ability to tolerate high concentrations of Cuthus the potential to bioremediate Cu.The F. solani was found to be the best fungi with the potential to bioremediate Cu in soil followedby other potential fungi namely A. niger and A. tamarii. Further study is required to study on thosepotential fungal in order to understand better their mechanism in tolerance with high Cuconcentration and their toxicology profile before the use in the actual contaminated area